2010
DOI: 10.1159/000322010
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Regulatory Synergy Is Required to Allow Control of the TAC1 Locus by MEK/ERK Signalling in Sensory Neurones

Abstract: Changes in the expression of the neuropeptide substance P (SP) in different populations of sensory neurones are associated with the progression of chronic inflammatory disease. Thus, understanding the genomic and cellular mechanisms driving the expression of the TAC1 gene, which encodes SP, in sensory neurones is essential to understanding its role in inflammatory disease. We used a novel combination of computational genomics, primary-cell culture and mouse transgenics to determine the genomic and cellular mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 68 publications
(104 reference statements)
4
48
0
Order By: Relevance
“…Using these cells, we were unable to show that GAL5.1 could act as an enhancer of promoter activity. However, we have previously shown that many regulatory sequences are only able to act as enhancers in response to activation of an appropriate signal transduction cascade (Shanley et al, 2010(Shanley et al, , 2011. Thus, we were able to show that GAL5.1 acted as an enhancer of promoter activity following activation of the PKC pathway, which is known to modulate gene expression in the hypothalamus and amygdala, but not PKA or MAPkinase pathways.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Using these cells, we were unable to show that GAL5.1 could act as an enhancer of promoter activity. However, we have previously shown that many regulatory sequences are only able to act as enhancers in response to activation of an appropriate signal transduction cascade (Shanley et al, 2010(Shanley et al, , 2011. Thus, we were able to show that GAL5.1 acted as an enhancer of promoter activity following activation of the PKC pathway, which is known to modulate gene expression in the hypothalamus and amygdala, but not PKA or MAPkinase pathways.…”
Section: Discussionmentioning
confidence: 70%
“…ECR2 could only drive tissue-specific expression in the presence of the endogenous TAC1 promoter whereas GAL5.1 can support expression in the presence of an exogenous weak promoter such as the human b-globin promoter or HSV-TK promoter. These observations suggest that different enhancers possess varying levels of autonomy or interdependence and that the GAL5.1 is functionally self-contained relative to some other previously characterized enhancers (Shanley et al, 2010(Shanley et al, , 2011.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Our own studies on the endogenous expression of the neuropeptide, substance P encoded by the TAC1 gene demonstrated that although the gene itself from 5′ to 3′ UTR was 8kb, we required a DNA fragment of 350kb to reproduce the appropriate expression patterns 30 , 31 . Subsequently our collaborators demonstrated key regulatory domains were as far as 250 kb and 100 kb 5′of the TAC1 gene 32 . The 350kb TAC1 fragment as a transgenic insertion demonstrated not only the well characterized rodent expression of TAC1, but as was the case with the SLC6A4 VNTR, it also demonstrated human specific TAC1 expression patterns and we again argued that the DNA was taking advantage of the complement of transcription factor that was present in the cells when the DNA in the regulatory regions evolved to support distinct transcription profiles for this gene.…”
Section: How Do Hominid Specific Sva Regulatory Domains Utilize the Ementioning
confidence: 99%